Fuzzy Sliding Mode Control of a Switched Reluctance Motor. (2016) - Prasad, K.M. Arun; Unnikrishnan, A.; Nair, Usha
Abstract: The simplicity, ruggedness, and low cost of a switched reluctance motor (SRM) makes it a viable candidate for various general-purpose adjustable-speed and servo-type applications. Sliding mode control (SMC) is one of the popular strategies to deal with uncertain control systems. The Fuzzy Sliding Mode Controller (FSMC) combines the intelligence of a fuzzy inference system with the sliding mode controller.PI controllers are generally used for the speed control of SRM main drawback of PI controller is high overshoot and large settling time. The main reason for this high overshoot and large settling time is due to the fixed nature of the controller parameters. In this paper, mathematical modelling of 6/4 SRM has been developed, speed performance of the motor using PI controller and FSMC has been analysed. Results of this study show that the overshoot is completely eliminated and the speed of response is improved when Fuzzy SMC is used for the speed control of SRM.